The Bloom's syndrome helicase promotes the annealing of complementary single-stranded DNA - Cheok, Chit Fang (Oxford University Press, 2005)
The product of the gene mutated in Bloom's syndrome, BLM, is a 3′–5′ DNA helicase belonging to the highly conserved RecQ family. In addition to a conventional DNA strand separation activity, BLM catalyzes both the disruption of non-B-form DNA, such as G-quadruplexes, and the branch migration of Holliday junctions. Here, we have characterized a new activity for BLM: the promotion of single-stranded DNA (ssDNA) annealing. This activity does not require Mg(2+), is inhibited by ssDNA binding proteins and ATP, and is dependent on DNA length. Through analysis of various truncation mutants of BLM, we show that the C-terminal domain is essential for strand annealing and identify a 60 amino acid stretch of this domain as being important for both ssDNA binding and strand annealing. We present a model in which the ssDNA annealing activity of BLM facilitates its role in the processing of DNA intermediates that arise during repair of damaged replication forks.